2014
DOI: 10.1242/dev.105874
|View full text |Cite
|
Sign up to set email alerts
|

Cyp26 enzymes are required to balance the cardiac and vascular lineages within the anterior lateral plate mesoderm

Abstract: Normal heart development requires appropriate levels of retinoic acid (RA) signaling. RA levels in embryos are dampened by Cyp26 enzymes, which metabolize RA into easily degraded derivatives. Loss of Cyp26 function in humans is associated with numerous developmental syndromes that include cardiovascular defects. Although previous studies have shown that Cyp26-deficient vertebrate models also have cardiovascular defects, the mechanisms underlying these defects are not understood. Here, we found that in zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 50 publications
(103 reference statements)
8
56
0
Order By: Relevance
“…Increases in RA signaling can inhibit cardiomyocyte specification, while decreases in RA signaling can promote cardiomyocyte specification (Keegan et al, 2005; Rydeen and Waxman, 2014; Waxman and Yelon, 2009). Interestingly, examining heart morphology, cell number, and cardiomyocyte marker expression, we found that the hearts of vp-rar mRNA-injected Tg(-5.1myl7:DsRed-NLS) f2 embryos (Mably et al, 2003) were enlarged, had increased cell number, and increased cardiomyocyte marker expression at 48 hpf (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Increases in RA signaling can inhibit cardiomyocyte specification, while decreases in RA signaling can promote cardiomyocyte specification (Keegan et al, 2005; Rydeen and Waxman, 2014; Waxman and Yelon, 2009). Interestingly, examining heart morphology, cell number, and cardiomyocyte marker expression, we found that the hearts of vp-rar mRNA-injected Tg(-5.1myl7:DsRed-NLS) f2 embryos (Mably et al, 2003) were enlarged, had increased cell number, and increased cardiomyocyte marker expression at 48 hpf (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6B-B3, D-D3, E), which suggests the vp-rar expression can promote cell non-autonomous loss of RA signaling. Next, to determine if the cell non-autonomous effects of vp-rar expression were dependent on Cyp26a1, we transplanted RA sensor donor cells into WT hosts or hosts co-injected with vp-rar mRNA and previously characterized cyp26a1 MOs (D’Aniello et al, 2013; Rydeen and Waxman, 2014). In contrast to when RA sensor cells were transplanted into vp-rar mRNA injected hosts, we found that depletion of Cyp26a1 in vp-rar mRNA injected host embryos results in RA sensor donor cells with robust GFP expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations